The ground beetles (Coleoptera: Carabidae) of the Strandzha Mountain and adjacent coastal territories (Bulgaria and Turkey) - Kostova, Rumyana (Biodivers Data J, 2016)
Abstract. BACKGROUND: The knowledge of the ground-beetle fauna of Strandzha is currently incomplete, and is largely based on data from the Bulgarian part of the region and on records resulting from casual collecting. This study represents a critical revision of the available literature, museum collections and a three years field study of the carabid beetles of the Bulgarian and Turkish parts of Strandzha Mountain and the adjacent Black Sea Coast territories. NEW INFORMATION: A total of 328 species and subspecies of Carabidae, belonging to 327 species from the region of Strandzha Mountain and adjacent seacoast area, have been listed. Of these, 77 taxa represent new records for the Bulgarian part of the region, and 110 taxa new records for Turkish part of the studied region. Two taxa, one subgenus (Haptotapinus Reitter, 1886) and one species (Pterostichus crassiusculus), are new to the fauna of Bulgaria. Based on a misidentification, the species Apotomus testaceus is excluded from the list of the Bulgarian fauna. Seven species (Carabus violaceus azurescens, Apotomus rufus, Platynus proximus, Molops alpestris kalofericus, M. dilatatus angulicollis, Pterostichus merklii, and Calathus metallicus) are treated as doubtful for the regional fauna, and one (Apotomus rufus) also for the Bulgarian fauna. Altogether, 43 taxa collected in the Turkish part of the region are new for European Turkey. New taxa for Turkey are the genera Myas and Oxypselaphus, the subgenus Feronidius, and nine species and subspecies (Carabus granulatus granulatus, Dyschirius tristis, Bembidion normannum apfelbecki, B. subcostatum vau, Acupalpus exiguus, Myas chalybaeus, Oxypselaphus obscurus, Pterostichus leonisi, Pt. melas). In addition, there are a further seven species that are here confirmed for Turkey.